Regulation of Pulmonary Vascular Smooth Muscle Contractility in Pulmonary Arterial Hypertension: Implications for Therapy - Lyle, Melissa A.; Davis, Jonathan P.; Brozovich, Frank V. (Frontiers in Physiology, 2017)
There are two primary components that produce PAH; aberrant structural changes (smooth muscle cell proliferation, smooth muscle cell hypertrophy and the deposition of matrix proteins within the media of pulmonary arterial vessels), and excess vasoconstriction. However, in PAH, the target and aim of all current therapeutic agents is to reduce the contractility of the pulmonary vasculature; prostaglandins, phosphodiesterase inhibitors, guanylate cyclase stimulators, endothelin antagonists, NO inhalation & Rho kinase inhibitors all influence signaling pathways in the pulmonary vascular smooth muscle to decrease vasoconstriction, and hence, pulmonary vascular resistance. This review will therefore primarily focus on discussing the signaling pathways regulating contractility in pulmonary vascular smooth muscle, the mechanism for current treatments, as well as highlighting potential targets for the development of novel therapies.